SYNTHESIS, MOLECULAR DOCKING, DYNAMICS ANALYSIS STUDIES, AND CYTOTOXICITYACTIVITY EVALUATION OF NOVEL BERBERINE DERIVATIVE BEARING OXADIAZOLE AND o-DIAMINOBENZENE MOIETIES - Xiaofei Jiang; Yangming Jiang; Qing Li; Lulin Li; Daoping Wang (Química Nova)
Berberine represents a prominent compound with commendable antitumor activity, a novel berberine derivative with substituted o-diaminobenzene moiety linked at the 9-position through oxadiazole and alkyl chain is designed, synthesized by reference to the histone deacetylase (HDAC) inhibitor structure mode through selective demethylation, substitution, hydrazolysis, acylation, cyclization, elimination, condensation reaction. The structures of these synthetic derivatives were characterized and confirmed by 1H NMR (nuclear magnetic resonance), 13C NMR, and MS (mass spectrometry) spectral data and finally evaluated for antitumor activities against MHCC97H, HCC827, HELA, and HEL cell in vitro by MTT (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide) method. The results demonstrated that target compound 8 exhibited better antiproliferative activity against the MHCC97H cell line, with a half maximal inhibitory concentration (IC50) = 5.4 ± 0.45 μM L−1 superior to berberine, and the activity against MHCC97H was nearly close to the reference drug doxorubicin. Through the dynamics of molecular docking and simulation, further analysis has demonstrated that the target compound 8 can form effective interactions with the HDAC6 target protein, and the results of binding free energy also revealed a strong affinity between the compound 8 and the HDAC6 protein. The results of this study suggest that compound 8 may be a potential inhibitor of HDAC6, which could have promising applications in the treatment of certain cancers.